The selective hydrogenation of furfural over supported palladium nanoparticle catalysts prepared by sol-immobilisation: effect of catalyst support and reaction conditions. Issue 1 (28th November 2017) - Albilali, Reem; Douthwaite, Mark; He, Qian; Taylor, Stuart H.
Abstract : Pd-TiO2 nanoparticles prepared by sol-immobilisation are very active for selective hydrogenation of furfural under mild conditions, and addition of Pt enhances performance to achieve a 95% yield of tetrahydrofurfuryl alcohol. Abstract : The selective hydrogenation of bio-derived furfural was investigated under mild conditions using a series of supported palladium catalysts prepared by a sol-immobilisation technique. Catalysts using alumina and titania supports were more selective towards tetrahydrofurfuryl alcohol. The catalytic activity of 1.19% Pd/TiO2 was evaluated under different reaction conditions and higher selectivity towards tetrahydrofurfuryl alcohol was observed when using 2-propanol as a solvent, and the yield of tetrahydrofurfuryl alcohol decreased as reaction temperature increased. The performance of the Pd catalyst was enhanced by the addition of Pt and a 95% yield of tetrahydrofurfuryl alcohol was achieved. The catalysts were characterised using a range of techniques, and the synergistic effect of adding Pt to Pd was due to an electronic promotional effect.